INTEGRATING ARTIFICIAL INTELLIGENCE IN ACHIEVING SDG 3, 4, AND 13 IN UTTARAKHAND - Dr. Prashant Kumar (International Educational Journal of Science and Engineering, 2025)
This research explores the integration of Artificial Intelligence (AI) in advancing Sustainable Development Goals (SDGs) 3 (Good Health and Well-being), 4 (Quality Education), and 13 (Climate Action) in the Himalayan state of Uttarakhand, India. With over 69% of its population living in rural areas and limited digital infrastructure, the state faces unique developmental challenges. The study highlights how AI-driven tools such as telemedicine platforms (eSanjeevani), adaptive learning systems, and climate prediction models are transforming public health, education, and environmental monitoring in remote regions. Empirical evidence shows AI’s positive impact, including 470,000+ teleconsultations, 57% female healthcare usage, and 85% accuracy in landslide predictions. However, digital divides, data scarcity, and ethical concerns present barriers to equitable implementation. The paper concludes with recommendations to establish AI research hubs, scale pilot projects, enhance digital literacy, and develop open data ecosystems to sustainably harness AI for inclusive development.